Microarrays: their design and use - Tomlinson, Craig R. (Henry Stewart Talks, 2009)
The use of microarrays to study genomic DNA and expressed RNA at a global level are being developed at a phenomenal pace in the basic and medical sciences, The basics of microarrays, Fundamental descriptions and issues regarding experimental design, high-throughput approaches, analysis, and bioinformatics, Different microarray platforms can be used to examine single nucleotide polymorphisms (SNP) of the genome, differential mRNA levels, differential microRNA (miRNA) levels, DNA methylation, genomic deletions and additions, DNA binding sites, and transcription rates, Microarrays in the diagnosis, prognosis, and treatment of disease, Microarrays in evolution, ecology and toxicology, The future of microarray technology
Archived at 2021/02/25